A precision measurement of the mass of the top quark. - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alton, A; Alves, G; et al. (2004)
The standard model of particle physics contains parameters--such as particle masses--whose origins are still unknown and which cannot be predicted, but whose values are constrained through their interactions. In particular, the masses of the top quark (M(t)) and W boson (M(W)) constrain the mass of the long-hypothesized, but thus far not observed, Higgs boson. A precise measurement of M(t) can therefore indicate where to look for the Higgs, and indeed whether the hypothesis of a standard model Higgs is consistent with experimental data. As top quarks are produced in pairs and decay in only about 10(-24) s into various final states, reconstructing their masses from their decay products is very challenging. Here we report a technique that extracts more information from each top-quark event and yields a greatly improved precision (of +/- 5.3 GeV/c2) when compared to previous measurements. When our new result is combined with our published measurement in a complementary decay mode and with the only other measurements available, the new world average for M(t) becomes 178.0 +/- 4.3 GeV/c2. As a result, the most likely Higgs mass increases from the experimentally excluded value of 96 to 117 GeV/c2, which is beyond current experimental sensitivity. The upper limit on the Higgs mass at the 95% confidence level is raised from 219 to 251 GeV/c2.